PASANG SURUT TAREKAT QADIRIYAH WA NAQSYABANDIYAH DI PANGGUL TRENGGALEK (1968-1998) - Anma Muniri (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2021)
ABSTRACT Tarekat is a Sufistic path taken by a follower through the murshid as someone who becomes a role model. One of the most massive tarekat in Panggul, Trenggalek is the Qadariyyah wa Naqsyabandiyah (TQN) order. The first TQN was brought by Kyai Makki Muharram from Kediri and then took Kyai Ngakasah to become a murshid in 1968. The Kyai's role was very large in spreading TQN in Panggul, Trenggalek. It is proven that there are three large Islamic boarding schools that are cared for by well-known kiai such as the Sabilul Hidayah Islamic Boarding School which is cared for by Kyai Zainal Abidin, the Al Huda Islamic Boarding School which is managed by Kyai Tohir and the Nglebeng Islamic Boarding School which is cared for by Kyai Ngakasah which is very influential in the spread of TQN. The purpose of this study was to reveal the history of TQN in Panggul 1968-1998. This study uses historical research methods using a qualitative approach. There are several findings in this study. First, the massive background of TQN in Panggul Trenggalek. Second, the influence of kyai and pondok pesantren in the spread of TQN. Third, the influence of Islamic boarding schools as the center of TQN development.Keywords: Islamic Boarding School, Kiai, Panggul Trenggalek, TQN